Efeitos da massa molar e do pH sobre o equilíbrio termodinâmico do sistema bifásico aquoso PEG/fosfatos - Juliana Ferrari Ferreira (Exacta, 2009)
Aqueous two-phase systems have been largely used in research for separation and purification of biomolecules. These systems are obtained through the mixture of two polymers or one polymer and a salt solution. The main subject of this work was the characterization of aqueous two-phase systems from different poly (ethylene glycol) with molecular weights of 1500, 4000 and 6000 and potassium phosphate salts at pH varying from 6 to 8 at standard conditions. It was observed a displacement of the binodal towards lower polymer concentrations when PEG molecular weights increased. On the other hand, the variation of pH did not promote significant alterations on the binodal. In the tie lines, it was not possible to stabilize the values of compositions influence, even when the polymers had been compared with themselves and different pHs.